1991
DOI: 10.1177/001872089103300304
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integration of Training Theory and Technique

Abstract: Reviewers of the training literature have generally concluded that training theory and practice are not well integrated, and that research findings are not often translated into useful training methods. In an effort to bridge the gap between training theory and practice, an organizing framework for conceptualizing training research is presented. The purpose of the framework is to highlight the linkages between training-related theory and technique in the areas of training analysis, design, and evaluation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…We suggest that there is still difficulty infiltrating operational communities with the results of team performance and training efforts. This problem is certainly not limited to CRM training; we have maintained that the application of research results to practice is a problem confronted by many areas of applied psychology (Cannon-Bowers, Tannenbaum, Salas, & Converse, 1991;Salas, CannonBowers, & Blickensderfer, 1997).…”
Section: Reciprocity Between Training Research and Practicementioning
confidence: 99%
“…We suggest that there is still difficulty infiltrating operational communities with the results of team performance and training efforts. This problem is certainly not limited to CRM training; we have maintained that the application of research results to practice is a problem confronted by many areas of applied psychology (Cannon-Bowers, Tannenbaum, Salas, & Converse, 1991;Salas, CannonBowers, & Blickensderfer, 1997).…”
Section: Reciprocity Between Training Research and Practicementioning
confidence: 99%
“…In addition, there is a need to apply relevant theories to guide the generation of hypotheses about training system design, and to provide a basis upon which to make design decisions (Cannon-Bowers, Tannenbaum, Salas, & Converse, 1991).…”
Section: Problemmentioning
confidence: 99%
“…In particular, there have been a number of studies that have shown that training motivation is related to trainee reactions (e.g., Mathieu et al, 1992;Tannenbaum et al, 1991), learning (e.g., Baldwin et al, 1991;Clark, 1990;Hicks, 1984;Mathieu et al, 1992), performance/transfer (e.g., Baldwin et al, 1991;Facteau, Dobbins, Russell, Ladd, & Kudisch, 1992;Ralls & Klein, 1991), and completion of training (Biersner et al, 1977;Mobley et al, 1979).…”
Section: Technical Report 93-011mentioning
confidence: 99%
“…However, the task had fairly high real-work validity (as noted, it is used to train real pilots), thereby increasing somewhat the generalizability of obtained results. Furthermore, this experiment can be considered a first step in designing theory-based training as prescribed by CannonBowers, Tannenbaum, Salas, and Converse (1991). Follow-up research is required in the field so that training interventions can be tested and refined in actual task settings.…”
mentioning
confidence: 99%